Research on Optimization of Friction Performance of Minicar Wheel Bearing Grease - Wu Jiang; Mo Yimin; Liu Qingchun; Wei Xuejun (Jixie chuandong)
To explore the effect of grease on the friction performance of minicar wheel bearings, a certain mini car is used as the research object, and the friction torque analysis model of wheel hub bearings is established using SKF rolling bearing calculation theory to study the effect of different grease parameters on the friction performance of wheel hub bearings. The friction performance of the wheel bearing grease is optimized and verified by combining the grease performance test, the wheel bearing friction torque test and the vehicle sliding test. Studies have shown that low viscosity grease with good oil separation performance is of great significance in reducing wheel bearing friction torque and improving vehicle fuel economy. The use of complex lithium-based synthetic hydrocarbon grease can reduce the low wheel bearing friction torque by 40% and the sliding resistance of the vehicle by 7.3%.